(untitled) (Mustansiria Dental Journal, 2018)
The role of smoking in periodontal disease has been extensively studied for many years. Many studies build up an increasing amount of scientific data which support the concept that tobacco use is an important risk factor for increasing of periodontal diseases. Intraoral radiographs are important for diagnosis of periodontal problems. The aim of this study is to estimate bone loss by using direct digital and conventional radiographs in smokers. One hundred eighty sites (for molar region except third molar) in cigarette smoking patients were examined by digital and conventional periapical radiograph for detection of alveolar bone loss according to sextants and severity of bone loss. All images were examined by measuring mesial and distal bone loss of molars. The study shows that the differences between the conventional and the digital images in estimation of alveolar bone loss were not the same in all mouth sextants, so more bone loss was indicated by digital image in the mandibular right and left sextants than conventional image while there was little differences in maxillary right and left sextants in both images. Also this study shows those highly significant differences in digital image than the conventional image in early bone loss but no significant differences in both moderate and severs bone loss.